1984
DOI: 10.1128/jcm.20.4.605-607.1984
|View full text |Cite
|
Sign up to set email alerts
|

Onset and duration of urinary antigen excretion in Legionnaires disease

Abstract: The purposes of this study were to determine whether antigen is excreted by patients with Legionnaires disease early enough after the onset of symptoms to be useful for making therapeutic decisions and whether antigen excretion ends when successful treatment is concluded. Specific antigen was detected in the urine of 14 (88%) of 16 patients with Legionnaires disease during days 1 to 3 of symptoms, 33 (80%) of 41 patients during days 4 to 7, 25 (89%) of 28 patients during days 8 to 14, and 11 of 11 patients aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
8

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(49 citation statements)
references
References 13 publications
(14 reference statements)
1
40
0
8
Order By: Relevance
“…Additional caveats include a small percent of patients that do not excrete the antigen and frequently the antigen can be detected for several weeks after infection, which complicates interpretation of the time-course of infection. 69,83 Studies vary greatly in the local species and serogroup distributions; likely components of actual geographic distribution of the organism and reporting bias. In one study, half of all sporadic cases over a 15 year period were due to species other than L. pneumophila serogroup 1.…”
Section: Clinical Laboratory Diagnosticsmentioning
confidence: 99%
“…Additional caveats include a small percent of patients that do not excrete the antigen and frequently the antigen can be detected for several weeks after infection, which complicates interpretation of the time-course of infection. 69,83 Studies vary greatly in the local species and serogroup distributions; likely components of actual geographic distribution of the organism and reporting bias. In one study, half of all sporadic cases over a 15 year period were due to species other than L. pneumophila serogroup 1.…”
Section: Clinical Laboratory Diagnosticsmentioning
confidence: 99%
“…Urine is, with the exception of patients in oliguric renal failure, an easily and non-invasively collected specimen. In addition it has previously been reported that urinary antigen is detectable as early as 1-3 days after the onset of the illness (Kohler et al, 1984) thus allowing a rapid diagnosis to be established. This latter finding was confirmed by this study (data not shown) in the few instances where appropriately timed urine specimens were available for examination.…”
Section: Discussionmentioning
confidence: 99%
“…192 Urine antigen for L. pneumophila is detectable in 80% to 89% of patients with legionnaires' disease beginning with the first 3 days of symptoms and continuing for at least 14 days; the duration of antigenuria was reduced by antibiotic therapy and was detectable for up to 42 days, especially in immunocompromised patients. 193 The urinary antigen assays are limited to detection of infections due to L. pneumophila serogroup 1 and not other Legionella serogroups or species. 94 Detection of fungal antigen in serum, urine, and other body fluids is used as an aid in the diagnosis of infections due to Cryptococcus neoformans, Aspergillus, H. capsulatum, and P. jirovecii.…”
Section: Nucleic Acid Testsmentioning
confidence: 99%